2018
DOI: 10.1002/jhet.3316
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Some New 6‐perfluoropropanyl Quinoline Derivatives

Abstract: A series of new quinoline derivatives containing perfluoropropanyl moiety were designed and synthesized. Their structures were confirmed by 1 H NMR, MS, and elemental analysis. The bioassay results showed that some of them exhibited good control efficacy against Pyricularia oryae. Also, some of the title compounds exhibited good insecticidal activity against Aphis craccivora Koch, Plutella xylostella, Mythimna Separate, and Tetranychus cinnabarinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The synthetic route was shown in Scheme . Generally, 2‐methyl‐4‐(perfluoropropan‐2‐yl)aniline was prepared from 2‐methyl aniline and 1,1,1,2,3,3,3‐heptafluoro‐2‐iodopropane reagent as starting materials according to our previous work . The mechanism of the key intermediate 2‐methyl‐4‐(perfluoropropan‐2‐yl)aniline was shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthetic route was shown in Scheme . Generally, 2‐methyl‐4‐(perfluoropropan‐2‐yl)aniline was prepared from 2‐methyl aniline and 1,1,1,2,3,3,3‐heptafluoro‐2‐iodopropane reagent as starting materials according to our previous work . The mechanism of the key intermediate 2‐methyl‐4‐(perfluoropropan‐2‐yl)aniline was shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic route was shown in Scheme 2. Generally, 2-methyl-4-(perfluoropropan-2-yl)aniline was prepared from 2-methyl aniline and 1,1,1,2,3,3,3-heptafluoro-2iodopropane reagent as starting materials according to our previous work [9][10][11][12][13]. The mechanism [37] [43], microwave method [44], Pfitzinger method [45], and one pot method [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterocyclic agrochemicals containing nitrogen has better activity, including insecticidal [4,5], antimicrobial [6], antiviral [7], fungicidal [8][9][10][11], and herbicidal [12]. Quinolines are one of the most important compounds in nitrogen-containing heterocycles and exhibited appreciable fungicidal activity [13][14][15]. For example, Quioxyfen is an effective antipowdery mildew agent.…”
Section: Introductionmentioning
confidence: 99%
“…1) is an active intermediate and possess excellent activity (93%) against rice blast at 3 mg/L [23]. In our previous work [13][14][15], a series of quinoline compounds were designed and synthesized; the bioassay results indicated that the quinoline compounds containing fluorine atom showed better fungicidal activity than other halo atom. Hence, a series of 2,3-dimethyl-4-(1-alkyl acetoxy)-6-tert-butyl-8-fluoroquinolines were designed, and their fungicidal activities were evaluated.…”
Section: Introductionmentioning
confidence: 99%